2015
DOI: 10.1136/jech-2014-204632
|View full text |Cite
|
Sign up to set email alerts
|

Objectively measured physical activity and vitamin D status in older people from Germany

Abstract: Although a positive dose-response relationship was seen between walking duration and the 25(OH)D serum level for most seasons, vitamin D insufficiency was still very prevalent even in high-active persons during all seasons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Being physically inactive and overweight were risk factors of lower serum 25(OH)D level in the US, but not in China. Several studies reported the positive association between physical activity and serum 25(OH)D level 37,38 . Physical activity increases sun exposure, and prevents loss of muscle strength and mass, which are the essential determinants of serum 25(OH)D level 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being physically inactive and overweight were risk factors of lower serum 25(OH)D level in the US, but not in China. Several studies reported the positive association between physical activity and serum 25(OH)D level 37,38 . Physical activity increases sun exposure, and prevents loss of muscle strength and mass, which are the essential determinants of serum 25(OH)D level 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity increases sun exposure, and prevents loss of muscle strength and mass, which are the essential determinants of serum 25(OH)D level 38 . However, evidence found that vitamin D insufficiency was still common among people who were highly physically active in Germany 37 . This probably partly contributes to the difference between China and the US.…”
Section: Discussionmentioning
confidence: 99%
“…Time spent outdoors in summer as well in winter are positive predictors. Because of the low intensity of the sun in winter, we do not think that this is a direct effect, but that it might be a reflection of physical activity and general health as well [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, lower amounts of physical activity are associated with both lower 25(OH)D[12, 26] and lower HDL-C.[27] Although we adjusted for physical activity in our analyses, this may not have fully accounted for the interaction between activity, 25(OH)D, and HDL-C. Few studies have thoroughly examined the relationship between 25(OH)D and HDL-C and our study adds to the literature by showing that further work needs to be done to investigate the potentially clinically meaningful impact of this association.…”
Section: Discussionmentioning
confidence: 99%